An in vitro comparative study to evaluate frictional resistance in sliding mechanics using different types of brackets and arch wires - حمودي , أحمد; فادي خليل (Latakia University Journal -Medical Sciences Series, 2024)
Aim: The aim of this study is to evaluate the impact of different types of bracket materials and wires on static friction values, to reach the best bracket/wire combination that achieves desired static friction values . Materials and Methods : Zweigle F 427 device was used to test the values of static friction of the different study groups. The study used (20) upper right canine MBT brackets with (0.022× 0.028 inch) slot size, distributed as follows ; (10) Mono crystalline Alumina bracket (MCA), and (10) metal brackets made of stainless steel (SS) , and (20) straight wire made of stainless steel with 0.017×0.025 inch dimension, (10) of which are traditional and (10) of which are coated with Teflon. The study was divided into four groups, each included five pairs; The first group; (5) stainless steel brackets – (5) stainless steel wire . The second ;(5) stainless steel brackets – (5) stainless steel wire coated with Teflon . The third; (5) MCA brackets – (5) stainless steel wire. The fourth; (5) MCA brackets – (5) stainless steel wire coated with Teflon . The study used a standardized ligation method for all groups, using 0.009 inch pre-formed steel ligation wire. The brackets were adhered to pre-formed metal rings using Cyano Acrylate Glue Adhesive (Alteco). Each couple was tested only once in order to eliminate any effect of wear. Results: Significant difference was observed between groups in the static friction values at a 95% confidence norm and P-value ˂ 0.05 . The samples of the second group had the lowest static friction values , followed by the first group , then the fourth group, and finally the third group. Conclusions: It is recommended to use (ss bracket/Teflon coated ss archwire) combination when low static friction values are needed, and (MCA bracket/ ss archwire) combination when high static friction values are needed .